FRI0460 SAFETY OF BIOLOGICAL AGENTS IN JUVENILE IDIOPATHIC ARTHRITIS: A META-ANALYSIS OF OBSERVATIONAL STUDIES. (2nd June 2020) - Cabrera, N.; Avila, G.; Belot, A.; Larbre, J. P.; Cattivelli, G.; Paredes, E.; Kassai, B.; Euvrard, R.; Grenet, G.; Berard, A.; Mainbourg, S.; Lega, J. C.
Abstract : Background: Follow-up cohorts (observational studies) were initiated consecutively or simultaneously to the development of randomised controlled trials (RCTs) in JIA patients (1, 2) . They help to identify many complications observed only in clinical practice related to off label use, coadministration of treatments, drug misuse, and occurrence of rare or unexpected event. In addition, observational studies include a higher number of patients with a longer duration of follow-up compared to randomised trials. Hence, they have a higher power to capture the occurrence of serious adverse events (SAE) in daily clinical practice 3 . Objectives: To estimate the incidence of serious adverse events (SAEs) including serious infections, malignancies, and death in patients with juvenile idiopathic arthritis (JIA) treated with biological agents (BAs) in daily clinical practice, using meta-analysis techniques. Methods: We systematically searched, up to May 2019, Medline and Embase databases for observational studies performed in JIA disease under BAs treatment. Outcomes were SAEs, serious infections, malignancies and all-cause mortality. Complementary, the incidence of SAEs in randomised controlled trials (RCTs) with withdrawal and parallel designs was performed by meta-analysis. Results: A total of 31 observational studies were included (6811 patients totalizing 17530 patients-years [PY] of follow-up). The incidence rate of SAEs was similar in observational cohorts and withdrawal RCTs (4.46 events per 100 PY, 95% CI 2.85- 6.38, I 2 = 95%) and 3.71 events per 100 PY (95%CI 0.0-13.34), I 2 = 56%, respectively). The incidence of SAE was lower in parallel RCT. The incidence rate of serious infections, malignancies and death in observational cohorts was estimated at 0.74 events per 100 PY (95%CI 0.32-1.30, I 2 =83%), 0.10 events per 100 PY (95% CI 0.06-0.16, I 2 =0%) and 0.09 events per 100 PY (95% CI 0.05-0.14, I 2 =0%), respectively. Infections were the known cause of death in 8 of the 14 deaths. In meta-regression and subgroup analysis, variation of serious infections rates were partially explained by follow-up time (R 2 = 30.3%, p= 0.0008), JIA categories (all JIA versus polyarticular versus systemic JIA categories, p= 0.001) and cohort quality (Newcastle-Ottawa score ≥ to 6 versus ≤ to 5 stars, p= 0.0025). Conclusion: Our results suggest that the incidence rate of SAEs related to BAs in JIA disease is similar to those observed in randomised withdrawal trials. The overall incidence remained low. However, unsatisfactory description of SAEs prevents analysis of hospitalisation causes. Infection and, to a lesser extent, cancer and death, explain only part of burden of BAs. References: [1]Berard RA, Laxer RM. Learning the hard way: clinical trials in juvenile idiopathic arthritis. Ann Rheum Dis. 2018;77(1):1–2. [2]Swart J, Giancane G, Horneff G, Magnusson B, Hofer M, Alexeeva Е, et al. Pharmacovigilance in juvenile idiopathic arthritis patients treated with biologic or synthetic drugs: combined data of more than 15, 000 patients from Pharmachild and national registries. Arthritis Res Ther. 2018 27;20(1):285. [3]Monti S, Grosso V, Todoerti M, Caporali R. Randomized controlled trials and real-world data: differences and similarities to untangle literature data. Rheumatol Oxf Engl. 2018 01;57(57 Suppl 7):vii54– Disclosure of Interests: None declared